Sikap Petani terhadap Pengolahan Kopi Robusta Berbasis Indikasi Geografis di Kabupaten Temanggung - Nuning Setyowati; Hanifah Ihsaniyati -; Aditya Pitara Sanjaya; Widiyanto - (Jurnal Penyuluhan, 2021)
Coffee is a superior commodity in Temanggung Regency. Post-harvest processing affects the quality of a coffee product. The Robusta Temanggung Coffee Geographical Indication Standard governs the standard of processing. This research aims to analyze the attitude of robusta coffee farmers towards GIs based coffee processing standards. The study uses a descriptive method. The respondents were 80 robusta coffee farmers in Temanggung Regency. Questionnaires are structured using a Likert scale. The data collection using random sampling techniques. The data analysis using the scoring method. The results showed that farmers had a good attitude towards GIs-based coffee processing standards, agreeing to GIs based sorting, drying, and storage processes. Farmers have not been motivated to measure coffee bean water content according to GIs standards due to facility constraints. Intensive education, motivation, facilities, and mentoring are required for farmers to implement GIs-based coffee processing standards.